Areas of nursing competence in acute wound care: A focus group study - Kielo-Viljamaa Emilia; Suhonen Riitta; Jalonen Leena; Stolt Minna (Elsevier B.V., 2022)
Background
Wound care is an essential part of registered nurses’ work. However, previous studies have indicated that registered nurses have limited competence in this area. Studies have also highlighted the lack of consistent and standardised areas of competence for registered nurses providing wound care.
Aim
To identify general areas of competence for registered nurses providing acute wound care during their transition from student to healthcare professional.
Methods
Focus group interviews were used to collect the data (N = 20). Separate focus groups were held for participants representing the following professions: (i) registered nurses; (ii) authorised wound care nurses; (iii) nurse educators; and (iv) physicians. The data were analysed using two-step inductive-deductive content analysis.
Findings
The two main competence areas for registered nurses who provide care for patients with acute wounds were: (i) knowledge, skills, and performance in aetiology and care; and (ii) wound management and assessment. These competence areas were divided into more detailed subcategories. The desired values and attitudes were as follows: respect for autonomy and privacy; holistic care; professionalism and courage; and economics related to wound care.
Discussion
Registered nurses play an essential role in the care and prevention of wounds. Nursing education on acute wound care could focus on the identified competence areas to cover the core competences for providing evidence-based, best-quality care for patients with acute wounds.
Conclusions
With consistent and structured competence areas, it would be possible to develop and improve wound care education and training at the undergraduate and postgraduate level.